1992
DOI: 10.5144/0256-4947.1992.544
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Pregnancy in King Fahad Hofuf Hospital: A Five Year Experience

Abstract: Out of a total of 45,836 deliveries over a five-year period (1986)(1987)(1988)(1989)(1990), 128 cases of ectopic pregnancy (0.28% incidence) managed during this period was compared with other previously published data in terms of presentation and management. There were no maternal deaths among the cases treated. The age distribution was 16-44 years with higher incidence 46 (36%) occurring in the range of 25-30. One hundred thirty (93%) were multipara. The presenting complaints included pain (100%), vaginal ble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…Studies from Saudi Arabia have also shown that almost 50% of women diagnosed with EP reported a history of PID and/or infertility. 30–33 Unfortunately, discussing sexually transmitted diseases in Islamic nations, especially in Saudi Arabia, is a very sensitive topic and therefore little is known about the role of sexually transmitted microbes in the pathogenesis of EP. 34 However, the few available governmental reports from the kingdom have shown that the annual incidence of chlamydial and gonococcal infections between 1995 and 1999 were 14.8 and 5.2 per 100,000 population, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from Saudi Arabia have also shown that almost 50% of women diagnosed with EP reported a history of PID and/or infertility. 30–33 Unfortunately, discussing sexually transmitted diseases in Islamic nations, especially in Saudi Arabia, is a very sensitive topic and therefore little is known about the role of sexually transmitted microbes in the pathogenesis of EP. 34 However, the few available governmental reports from the kingdom have shown that the annual incidence of chlamydial and gonococcal infections between 1995 and 1999 were 14.8 and 5.2 per 100,000 population, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…EP represents 1-2 % of all pregnancies and causes almost 10 % of all maternal deaths during the first trimester worldwide [18,22,24]. In Saudi Arabia, the reported prevalence of EP is 0.5 % and almost 50 % of cases had a history of pelvic inflammatory disease (PID) and/or infertility [2][3][4]31].…”
Section: Introductionmentioning
confidence: 99%